Isodeoxyelephantopin Inactivates Thioredoxin Reductase 1 and Activates ROS-Mediated JNK Signaling Pathway to Exacerbate Cisplatin Effectiveness in Human Colon Cancer Cells - Hong, Lin; Chen, Jundixia; Wu, Fang; Wu, Fengjiao; Shen, Xin; Zheng, Peisen; Shao, Rongrong; Lu, Kongqin; Liu, Zhiguo; Chen, Daoxing; Liang, Guang; Cai, Yuepiao; et al. (Frontiers in Cell and Developmental Biology, 2020)
Colon cancer is one of the leading causes of cancer-related death in the world. The development of new drugs and therapeutic strategies for patients with colon cancer are urgently needed. Isodeoxyelephantopin (ESI), a sesquiterpene lactone isolated from the medicinal plant Elephantopus scaber L., has been reported to exert antitumor effects on several cancer cells. However, the molecular mechanisms underlying the action of ESI is still elusive. In the present study, we found that ESI potently suppressed cell proliferation in human colon cancer cells. Furthermore, our results showed that ESI treatment markedly increased cellular reactive oxygen species (ROS) levels by inhibiting thioredoxin reductase 1 (TrxR1) activity, which leads to activation of the JNK signaling pathway and eventually cell death in HCT116 and RKO cells. Importantly, we found that ESI markedly enhanced cisplatin-induced cytotoxicity in HCT116 and RKO cells. Combination of ESI and cisplatin significantly increased the production of ROS, resulting in activation of the JNK signaling pathway in HCT116 and RKO cells. In vivo, we found that ESI combined with cisplatin significantly suppressed tumor growth in HCT116 xenograft models. Together, our study provide a preclinical proof-of-concept for ESI as a potential strategy for colon cancer treatment.